The Difficult School-To-Work Transition of High School Dropouts: Evidence from a Field Experiment - Pierre Cahuc; Stéphane Carcillo; Andreea Minea (Institute of Labor Economics (IZA), 2017)
This paper investigates the effects of the labor market experience of high school dropouts four years after leaving school by sending fictitious résumés to real job postings in France. Compared to those who have stayed unemployed since leaving school, the callback rate is not raised for those with employment experience, whether it is subsidized or non-subsidized, in the market or non-market sector, if there is no training accompanied by skill certification. In particular, we find no stigma effect associated with subsidized or non-market sector work experience. Moreover, training accompanied by skill certification improves youth prospects only when the local unemployment rate is sufficiently low, which occurs in one fifth of the commuting zones only.
Keywords: J08; J60; 330; youth; unemployment; training